Inovasi Aplikasi E-SDM dalam Meningkatkan Kualitas Manajemen Data Pegawai di Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kota Surabaya - Ananda Diane Masayu; Eva Hany Fanida; Meirinawati Meirinawati; Neny Ayu Nourmanita (Jurnal Hukum, Administrasi Publik dan Negara, 2026)
This study aims to analyze the innovation of the use of e-SDM Applications in improving the quality of digital employee data management at the Surabaya City Human Resources Development Agency (BKPSDM). This study uses a qualitative approach with a case study method through data collection techniques such as in-depth interviews, direct observation, and supporting documentation. The research analysis refers to the success factor model of e-Government innovation according to Maulidhia J.P., which includes aspects of leadership, stakeholders, resources, technology and information, processes, goals and values, and laws and regulations. The results of the study indicate that the implementation of e-SDM Applications can improve work efficiency, data accuracy, transparency, and ease of access to employee information through an integrated digital system. This success is supported by leadership commitment, collaboration between stakeholders, and the availability of adequate resources. However, this study also found several challenges, including technical system and network constraints, the need to increase human resource capacity, and the need for continuous regulatory and SOP updates. Overall, e-SDM innovations have made a positive contribution to improving the quality of employee data management in government environments.